Seleccion en generaciones tempranas de frijoles volubles en asociacion con maiz - Davis, J.; García, S.; Tejada, G (International Center for Tropical Agriculture, 1980)
Studies were conducted at CIAT to test a new methodology (1) to improve F3, yields through the use of a hierarchical exptl design (a 9 x 9 lattice with 3 replications, with lines grouped according to the design, without taking into accont the family of origin) and (2) to select beans in association with maize in search for a greater complementation between the 2 crops. Analysis of yield data was lst done on the basis of mean family yields (main plots) and afterwards on those of individual lines. A good correlation exists between the yields of bean famines in the F3 and their corresponding yields in the following generation. The advantage of this method over more traditional ones is that it is possible to eliminate entire families of limited potential already in the F3. The best lines are always found in the best families. The efficiency of the methodology is greater when families with more than one line are always used since the exptl error decreased as the no. of lines/family increased. This methodology is also good for evaluating the productivity of beans in association with maize. There are bean genotypes that combine better with maize; these desirable genotypes can already be detected in the F3 generation. (CIAT)